Impact of upper respiratory tract infections on perioperative outcomes of children undergoing therapeutic cardiac catheterisation. Issue 7 (22nd March 2018) - Zhang, S.; Ding, S.; Cai, M.; Bai, J.; Zhang, M.; Huang, Y.; Zheng, J.
Abstract : Background: Recent upper respiratory tract infection (URI) is associated with increased incidence of perioperative complications in children undergoing open heart surgery. As a result, surgery is often postponed. However, the effect of recent URI on the incidence of perioperative complications in children undergoing therapeutic cardiac catheterisation is unknown. We investigated the perioperative outcomes of congenital heart disease (CHD) children with recent URI who underwent elective therapeutic catheterisation. Methods: We prospectively included children treated for CHD. Before surgery, parents or legal guardians were interviewed to complete a questionnaire on the child's demographics, history of asthma and passive smoking, and URI symptoms. Recorded perioperative respiratory adverse events (PRAEs) included laryngospasm, bronchospasm, breath holding, oxygen desaturation, and severe cough. Information on postoperative dysphoria, fever, copious sputum, and vomiting was obtained by telephone 24 h after surgery. Results: Of 363 included children, 169 had recently (within 2 weeks) had a URI. The URI did not affect the incidence of laryngospasm, bronchospasm, breath holding, fever, or vomiting. The incidence of desaturation, severe cough, dysphoria, and copious sputum were significantly increased. Independent risk factors for PRAEs in children with a recent URI included age, passive smoking, and presence of rhinorrhoea or moist cough. The lengths of stay in the hospital and intensive care unit were not significantly different between groups. Conclusion: Although recent URI increased the incidence of PRAEs in children undergoing therapeutic cardiac catheterisation, most CHD patients with recent URI can undergo elective therapeutic cardiac catheterisation without serious adverse events or prolonged hospitalisation.